The Authority–Identity Relation: Symbolic References and Interpretative Authority in Postwar Kosovo. Issue 4 (2nd October 2017) - Distler, Werner
ABSTRACT: In postwar Kosovo, international and Kosovar political actors claiming authority in the democratization and statebuilding process lacked a long-standing 'authoritative relation' with each other and the citizenry. To analyse the structural conditions for the emergence of political authority, the article suggests applying the analytical framework of 'interpretative authority', which captures the relational character and simultaneity of authority generation by international and Kosovar actors. Given that Kosovo had unsecured symbolic conditions for authority – no commonly shared symbols of unity for all communities and no commonly agreed interpreter of symbols of unity – political actors were competing intensely for the identity and symbolizations of the 'new' Kosovo in their attempts to gain authority in various institutional opportunity structures. The competition over authority and the attempts to denationalize public communications made by the international administration, the United Nations Mission in Kosovo (UNMIK), led to the reimbursement of particularistic symbolic references of Kosovar actors, thereby keeping the unsecured symbolic conditions and the weakness of interpretative political authority in Kosovo stable.